2013
DOI: 10.3171/2013.7.spine13229
|View full text |Cite
|
Sign up to set email alerts
|

Upper cervical cord compression due to a C-1 posterior arch in a patient with ossification of the posterior longitudinal ligament and a kyphotic cervical spine in the protruded-head position

Abstract: In this paper the authors report the case of a patient with ossification of the posterior longitudinal ligament (OPLL) below the axial vertebra (C-2) at the kyphotic cervical spine, with an atlas vertebra (C-1) posterior arch that compressed the spinal cord with the head in a pathognomonic position, similar to a protruded position. This condition appears to be very rare. The morphological findings between the kyphotic cervical spine and OPLL, the upper occipitocervical junction, and the protruded-head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As symptomatic upper cervical cord compression and cervical OPLL occur simultaneously is quiet uncommon, there are only 12 studies (50 cases) reported in the English literature till today [ 6 , 7 , 13 , 16 24 ] (Table 3 ). Thus, the radiographic manifestations, as well as the surgical outcome of this disease, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As symptomatic upper cervical cord compression and cervical OPLL occur simultaneously is quiet uncommon, there are only 12 studies (50 cases) reported in the English literature till today [ 6 , 7 , 13 , 16 24 ] (Table 3 ). Thus, the radiographic manifestations, as well as the surgical outcome of this disease, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 ] Until now, only a few cases of upper cervical cord compression have been reported. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, canal stenosis at the level of the atlas was diagnosed by dynamic myelo-CT scan, 16) dynamic MRI, 22) or both of them 17) when no cause for myelopathy was detected with CT scan or MRI in the neutral position. Recent study reported that MR myelography can achieve a reliable diagnosis of lumbar spinal stenosis compared with CT myelogram.…”
Section: Discussionmentioning
confidence: 99%